Chronic Hepatitis C: Treatment, Complications, and Long-term Outcomes in a Population of Latino Veterans - Santiago-Rolón, Amarilys; Purcell, Dagmary; Grigg, Nicole; Toro, Doris H. (Puerto Rico Health Sciences Journal, 2016)
Objective: Chronic hepatitis C (CHC) is a major public health problem in Puerto Rico. It is the most common cause of chronic liver disease and the most frequent indication for liver transplantation in the United States. Our main objectives were to estimate the seroprevalence of CHC infection, to describe the demographic and histological parameters of the infection in our sample population, and to evaluate the treatment outcomes in Puerto Rican veterans. Methods: To determine overall seroprevalence, we reviewed all the hepatitis C cases (encompassing from January 1, 2002, to December 31, 2009) of the VA Caribbean Healthcare System, Department of Veterans Affairs. The records of only those individuals who received treatment with pegylated interferon and ribavirin were reviewed to determine risks factors for infection, response rates, adverse events, and outcomes. Results: During the study period, there were a total of 1,496 patients identified as being infected with HCV, for an estimated seroprevalence of 2.3%. Of these, approximately 10% (137) were treated with combination therapy and were included in this study. The mean age was 58 (±6.4); 96.4% were men. The most common genotype was type 1. The responses to treatment were generally poor, with only 48.4% of the patients achieving sustained virological response. Discussion: Though the seroprevalence of chronic hepatitis C in the Latino veteran population of Puerto Rico is high, relatively few patients have received treatment, most probably because of the contraindications of the medications used. Combination therapy with pegylated interferon plus weight-based ribavirin was inefficient and plagued with side effects; as a whole, this therapy was not found to be overly beneficial to our patients. New emerging and approved therapies will change this paradigm, allowing the treatment of a larger population without the side effects of the studied therapy.